Radiocarbon chronology of Middle and Upper Paleolithic sites in Serbia, Central Balkans. (June 2019) - Alex, Bridget; Mihailović, Dušan; Milošević, Stefan; Boaretto, Elisabetta
Abstract: The Central Balkans, in present-day Serbia, was a potentially dynamic zone during the Middle and Upper Paleolithic (MP-UP), as it is situated between hypothesized dispersal routes of modern humans and refuges of late Neanderthals. However, the population history of the region remains poorly understood because there are little chronometric data from Late Pleistocene sites in Serbia. Here, we review the existing paleoanthropological record for the MP-UP in the Central Balkans and surrounding areas. Then, we add to it by reporting radiocarbon dates from two Serbian cave sites, Pešturina and Hadži Prodanova, which contain Middle Paleolithic and Gravettian assemblages. The results provide reliable human occurrence-dates older than 39 ka calibrated radiocarbon years before present (cal BP) and between 34 and 28 ka cal BP. As shallow palimpsest deposits with low artifact yields, the sites are not ideal contexts for establishing chrono-cultural stratigraphy. However, it is proposed that the occupants before 39 ka cal BP were Neanderthals producing MP artifacts, while those after 34 ka cal BP were modern humans with Gravettian traditions. Highlights: Reviews paleoanthropological record of Middle-Upper Paleolithic in Serbia New radiocarbon dates reported for two MP-UP sites: Pešturina and Hadži Prodanova Sites contain material culture of Middle Paleolithic and Gravettian traditions. Radiocarbon dates indicate human presence before 39 and between 34 and 28 ka cal BP.